Sex body: A nest of protein mixture - Li, Miao (Frontiers in Cell and Developmental Biology, 2023)
During the pachytene stage in mammalian meiosis, the X and Y chromosomes remain largely unsynapsed outside the pseudoautosomal region, while autosomes are fully synapsed. Then, the sex chromosomes are compartmentalized into a “sex body” in the nucleus and are subjected to meiotic sex chromosome inactivation (MSCI). For decades, the formation and functioning of the sex body and MSCI have been subjects worth exploring. Notably, a series of proteins have been reported to be located on the sex body area and inferred to play an essential role in MSCI; however, the proteins that are actually located in this area and how these proteins promote sex body formation and establish MSCI remain unclear. Collectively, the DNA damage response factors, downstream fanconi anemia proteins, and other canonical repressive histone modifications have been reported to be associated with the sex body. Here, this study reviews the factors located on the sex body area and tries to provide new insights into studying this mysterious domain.